2003
DOI: 10.1002/asna.200310026
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray and optical properties of X‐ray sources in the 13hr XMM‐Newton/Chandra deep survey

Abstract: Abstract. The 13hr XMM-Newton/Chandra deep survey is the first of two extremely deep XMM-Newton fields observed by the XMM-OM consortium. A 120 ks Chandra mosaic, covering 0.2 deg ¾ , provides sensitive, confusion-free point source detection with sub-arcsecond positions, while the 200 ks XMM-Newton observation provides high quality X-ray spectroscopy over the same sky area. We have optical spectroscopic identifications for 70 X-ray sources. Of these, 42 are broad emissionline AGN with a wide range of redshifts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Therefore, the dilution of the AGN light by the host galaxy is mainly occurring at small redshift, supporting the fact that the intrinsic luminosity of the AGN has significantly declined as the redshift is decreasing. Page et al (2003) suggested that if the dilution hypothesis holds true, it may explain why a large fraction of unabsorbed X-ray sources lacking broad emission lines in their optical spectra are lying at a low redshift (the majority of our sources of this kind are lying at z < 0.5). The characteristic luminosity of AGN has declined dramatically (by a factor 10) since z = 2 in both the X-ray (Page et al 1997) and in the optical (Boyle et al 2000).…”
Section: Unabsorbed Agn Lacking Broad Emission Linesmentioning
confidence: 99%
“…Therefore, the dilution of the AGN light by the host galaxy is mainly occurring at small redshift, supporting the fact that the intrinsic luminosity of the AGN has significantly declined as the redshift is decreasing. Page et al (2003) suggested that if the dilution hypothesis holds true, it may explain why a large fraction of unabsorbed X-ray sources lacking broad emission lines in their optical spectra are lying at a low redshift (the majority of our sources of this kind are lying at z < 0.5). The characteristic luminosity of AGN has declined dramatically (by a factor 10) since z = 2 in both the X-ray (Page et al 1997) and in the optical (Boyle et al 2000).…”
Section: Unabsorbed Agn Lacking Broad Emission Linesmentioning
confidence: 99%
“…Finally, we have tested whether the lack of optical broad emission lines in unabsorbed NELGs can be explained in terms of AGN/host galaxy contrast (Lumsden et al 2001;Moran et al 2002;Page et al 2003;Severgnini et al 2003). To this end, we have compared the 2-10 keV luminosity distributions of two sub-samples of unabsorbed BLAGNs and NELGs detected with redshifts ranging from 0.17 to 0.7, where the redshift distributions of BLAGNs and NELGs overlap (see Fig.…”
Section: Excess Absorptionmentioning
confidence: 99%
“…Alternatively some objects might host an AGN with a non-standard accretion disk (Yuan & Narayan 2004). A final possibility is that some ALGs may have normal (unabsorbed) AGNs that could be hidden if the host galaxy is bright enough (Severgnini et al 2003;Page et al 2003).…”
Section: Algs X-ray Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…However the amount of observational results that cannot be explained in terms of the unified model of AGN is also significant. There is a substantial number of type-1 AGN for which X-ray absorption has been detected (Mittaz et al 1999;Fiore et al 2001;Page et al 2001;Schartel et al 2001;Tozzi et al 2001b;Mainieri et al 2002;Brusa et al 2003;Page et al 2003;Carrera et al 2004;Perola et al 2004;Mateos et al 2005), as well as Seyfert 2 galaxies unabsorbed in X-rays (Pappa et al 2001;Panessa et al 2002;Barcons et al 2003;Mateos et al 2005). The origin of the X-ray absorption in type-1 AGN is still not clear.…”
Section: Introductionmentioning
confidence: 99%